Analisis Pengaruh Gaya Kepemimpinan Kepala Sekolah terhadap Kinerja Guru dan Siswa - Daimah; Hikmatul Luklu’il Maknun (Bildung: Jurnal Ilmu Pendidikan, 2025)
The purpose of this research is to determine the general description of the leadership style of the head of MI AL MA'ARIF KEDUNGREJA, teacher performance, and its influence on the democratic leadership style of Madrasah leaders on the performance of MI AL MA'ARIF teachers. This survey is a qualitative survey with a democratic approach. This research aims to investigate the influence of the principal's leadership style on teacher performance in senior high schools. Qualitative research methods with case studies were carried out on one teacher and one school principal. The research results show that transformational and transactional leadership styles have a significant impact on teacher motivation, creativity and performance. An effective leadership style can improve the quality of education and improve the work environment. This research provides recommendations for school principals to develop leadership styles that suit the needs of teachers and students.